Hjartavöðvasjúkdómur meðal kvenna : algengi metið með hjartaómun og krufningu - Uggi Agnarsson; Þórður Harðarson; Jónas Hallgrímsson; Ásmundur Brekkan; Nikulás Sigfússon (Læknafélag Íslands, Læknafélag Reykjavíkur, 2009)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open The purpose of this study was to estimate the prevalence of hypertrophic cardiomyopathy (HCM) in a group of 3922 women randomly selected from the Reykjavik study, phase IV, in 1981-1983. Of these, 358 women (9%) had an abnormal (group A) and 3564 (91%) had a normal electrocardiogram (ECG). In 1989, an echocardiography (echo) study of all surviving women from group A as well as a matched echo control group of 89 women (group B) from cohorts with a normal ECG, was performed, to identify subjects with HCM as well as a review of autopsy data and death certificates from deceased cohorts. To December 1st 1989 there had been a total of 100 deaths, 18 from group A and 82 from cohorts with a normal ECG, but no deaths had occurred amongst 89 selected for group B. HCM was identified by echo in 4 of 274 women examined but 66 did not attend. No case of HCM was found from the 76 attendees in group B. Autopsy diagnosed five additional cases of HCM from the 100 deceased cohorts. Thus a total of 9 cases of HCM were found. Three of four women diagnosed by echo were symptomatic but only one of five diagnosed at autopsy had apparent symptoms prior to death. Two of the five died suddenly. A echo-Doppler study was performed on the 4 HCM cases and the results compared to 40 normal controls in group B. The results showed an increased ejection velocity (P<0.001) and an increased late diastolic contribution to left ventricular filling in subjects with HCM (P<0.001). The prevalence of HCM and 95% confidence interval was calculated. We found 1.5% (0.4-3.8%) prevalence of HCM in women with an abnormal ECG and a calculated prevalence of 0.14% (0.04-3.9%) in the total group of 3922 as diagnosed by echo. The overall calculated minimal prevalence of HCM in women 30 to 73 years was 0.2% (0.1-0.6%). Tilgangur þessarar rannsóknar var að meta algengi hjartavöðvasjúkdóms (HVS) í hópi 3922 fullorðinna kvenna, þátttakendum í hópþýði ...